Assessment of green development strategies for manufacturing industry in China's coastal regions under dual-carbon circular economy using analytic hierarchy process - Jiang, Lihong (Frontiers in Public Health, 2025)
IntroductionChina's coastal manufacturing industry is fundamental to advancing national ecological modernization. Its effective green transition is critical for attaining sustainable development. This study investigates the key elements of this industry's green development, operating within the context of a dual-carbon circular economy, and assesses its current progress.MethodsA multilayered evaluation framework was developed using the Analytic Hierarchy Process (AHP). This methodology was employed to identify and prioritize crucial factors influencing the green development of the coastal manufacturing industry. Furthermore, the study systematically examined the multidimensional impacts of three principal AHP-derived factors on the industry's quality of green development.ResultsThe analysis indicates a consistent improvement in the overall quality of green development within the industry. However, the findings also highlight several significant challenges. Specifically, there is an urgent requirement to bolster the green system, a need to fully leverage the transformative capabilities of green innovation, and a necessity to address the inconsistent pace of green transformation observed across different regions.DiscussionThe steady enhancement in green development quality is a positive trend, yet the identified challenges underscore areas requiring immediate attention and strategic intervention. To expedite the green transformation of the manufacturing sector, it is recommended that enterprises refine their green development strategies by capitalizing on their unique strengths. Simultaneously, government agencies should amplify their policy support and resource allocation to foster and steer this transition toward achieving China's broader ecological and sustainable development objectives.